Menelusuri Jejak Tarekat: Sejarah, Teosofi dan Perkembangannya di Indonesia - Qhotrunnada, Naila Rizqi (Maliki Interdisciplinary Journal, 2025)
Tarekat is a religious institution that plays an important role in the social, cultural and political life of Indonesian society. With a focus on the Qadiriyah, Syadziliyyah, and Naqsyabandiyah orders. Tarekat not only functions as a pathway for fostering spiritual values, but also makes a real contribution instrengthening social solidarity, solving community problems, and building the moral character of society. This study uses library research with historical and sociological analysis to trace the development and adaptation of tarekat from the classical period to the contemporary era. In the modern context, tarekat has experienced revitalization through digital media, such as online dhikr assemblies and urban-based recitation communities, showing its resilience in facing the challenges of globalization. Thus, tarekat remains relevant as a spiritual and social force in the dynamics of Indonesian society.